What are the Factors that Affect the Risk of Parenting Stress in Mothers with Disability Children? A New Evidence from Sukoharjo, Central Java - Fikriyyah, Syarifatul; Adriani, Rita Benya; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Mothers play an important role in the care of children with physical and psychological disabilities. However, the role of caring children with disabilities can cause stress for the mother. Parenting stress can lead to anxiety, emotional instability, and avoidance of the environment in mother. This, in turn, may deteriorate the quality of family life. As a result, children with disabilities may experience development and growth disorders. This study aimed to determine the factors that affect the parenting stress in the caring of children with disability in Sukoharjo District, Central Java.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted at Sanggar Inklusi, Sukoharjo, Central Java, from February to March 2018. A sample of 163 mothers with disabled children was selected for this study by exhaustive sampling. The dependent variable was parenting stress. The independent variables were adversity intelligence, disability level, maternal education, maternal employment status, family income, and family support. The data were collected by questionnaire and analyzed by path analysis.Results: The risk of maternal parenting stress increased with children disability (b= 4.64, SE= 1.72, p= 0.07) and mothers working outside the house (b= 1.68, SE= 0.93, p= 0.069). The risk of maternal parenting stress decreased with high adversity intelligence (b= -0.28, SE= 0.12, p= 0.016), high maternal education (b= -8.50, SE= 0.86, p< 0.001), high family income (b= -0.28, SE= 0.16, p= 0.078), and strong family support (b= -0.22, SE= 0.08, p= 0.007).Conclusion: The risk of maternal parenting stress increases with high children disability and maternal employment status, but decreases with high adversity intelligence, high maternal education, high family income, and strong family support.Keywords: parenting stress, children, disabilityCorrespondence:SyarifatulFikriyyah. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: vivisyarifah@yahoo.com. Mobile: +6285642009597Journal of Maternal and Child Health (2018), 3(2): 156-165https://doi.org/10.26911/thejmch.2018.03.02.08